(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Osteoporosis is most common bone disease in elders, which is defined by loss of bone density with higher risk of bone fracture. Many studies have focused on relationship of vitamin D receptor (VDR) gene variation and risk of osteoporosis in postmenopausal women. However, ApaI VDR gene polymorphism is sparely reported among Thai population. This study was proposed to evaluate genotypic polymorphism of ApaI (T>G; rs7975232) VDR gene polymorphism between risk and control groups in postmenopausal women. In addition, bone mineral density (BMD) screening and other bone related markers were also measured. Results was shown that BMI, BMD, calcium and ALP of risk and control groups were significantly different. Mean of BMI in control group was trended to overweight and mean of BMD in risk group was osteopenia. Therefore, calcium and ALP in both groups were within reference range. The genotypic frequencies of risk group were 15.2% (n = 7) wild type (TT); 63.1% (n = 29) heterozygous variant (TG); and 21.7% (n = 10) homozygous variant (GG). Controls were 16.7% (n = 4) wild type (TT); 70.8% (n = 17) heterozygous variant (TG); and 12.5% (n = 3) homozygous variant (GG). Odd ratio of osteoporosis in ApaI heterozygous (TG) and homozygous (GG) variants were significantly increased in risked postmenopausal women (p<0.02 and <0.001, respectively). Homozygous variant (GG) was highest OR value (OR = 1.90, 1.04-4.32). Genotypic of ApaI VDR gene is useful to evaluate occurrence of osteoporosis especially in Thai postmenopausal women who are carried homozygous variant.